2020
DOI: 10.26508/lsa.202000720
|View full text |Cite
|
Sign up to set email alerts
|

The bacterial quorum sensing signal DSF hijacks Arabidopsis thaliana sterol biosynthesis to suppress plant innate immunity

Abstract: Quorum sensing (QS) is a recognized phenomenon that is crucial for regulating population-related behaviors in bacteria. However, the direct specific effect of QS molecules on host biology is largely understudied. In this work, we show that the QS molecule DSF (cis-11-methyl-dodecenoic acid) produced by Xanthomonas campestris pv. campestris can suppress pathogen-associated molecular pattern–triggered immunity (PTI) in Arabidopsis thaliana, mediated by flagellin-induced activation of flagellin receptor FLS2. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 131 publications
3
23
0
Order By: Relevance
“…Two lines expressing FLS2-GFP under the control of its native promoter were crossed with FER knock-out alleles fer-2 and fer-4 . In line with previous reports ( Bücherl et al, 2017 ; Tran et al, 2020 ), we observed that FLS2-GFP localized to laterally stable foci in wild-type (WT) ( Figure 1—video 1 ). Consistently, FLS2-GFP single-particle trajectories exhibited a confined mobility behavior ( Figure 1—figure supplement 1 , Figure 1—video 1 ).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Two lines expressing FLS2-GFP under the control of its native promoter were crossed with FER knock-out alleles fer-2 and fer-4 . In line with previous reports ( Bücherl et al, 2017 ; Tran et al, 2020 ), we observed that FLS2-GFP localized to laterally stable foci in wild-type (WT) ( Figure 1—video 1 ). Consistently, FLS2-GFP single-particle trajectories exhibited a confined mobility behavior ( Figure 1—figure supplement 1 , Figure 1—video 1 ).…”
Section: Resultssupporting
confidence: 93%
“…Using this approach, we found that FLS2-GFP fluorescence was maintained into well-defined and static structures in WT, while it appeared more disperse and more mobile in both fer mutants ( Figure 1A and B , Figure 1—figure supplement 2 ). To substantiate these observations, we used the previously established spatial clustering index (SCI), which describes protein lateral organization ( Gronnier et al, 2017 ; Tran et al, 2020 ). As expected, SCI of FLS2-GFP was lower in fer-4 than in WT ( Figure 1C ), indicating disturbance in FLS2-GFP lateral organization.…”
Section: Resultsmentioning
confidence: 99%
“…Two lines expressing FLS2-GFP under the control of its native promoter were crossed with two FER knock-out alleles, fer-2 and fer-4. In line with previous reports (Bücherl et al, 2017;Tran et al, 2020), we observed that FLS2-GFP localizes to static foci in the wild-type (WT) (Movie S1). Consistently, FLS2-GFP single particle trajectories exhibit a confined mobility behavior (Fig.…”
Section: Fer Regulates Membrane Nanoscale Organization Of Fls2 and Bak1supporting
confidence: 92%
“…1A-B and S2). To substantiate these observations, we used previously established spatial clustering index (SCI) which describes protein lateral organization (Gronnier et al, 2017;Tran et al, 2020). As expected, SCI of FLS2-GFP was lower in fer-4 than in WT (Fig.…”
Section: Fer Regulates Membrane Nanoscale Organization Of Fls2 and Bak1mentioning
confidence: 76%
“…This is especially relevant since the activity of receptors might be dependent on nanodomains. The liquid-ordered phases of nanodomains comprise a particular lipid composition and, e.g., are enriched in sterols and sphingolipids [ 47 , 48 ]. In addition, early responses such as extracellular alkalinization and ion fluxes are associated with the plasma membrane, and membrane dynamics have been shown to regulate the response to flagellin by internalizing the receptor FLS2 [ 49 ].…”
Section: Discussionmentioning
confidence: 99%